Pengaruh Promosi Digital, Potensi Keuntungan, dan Risiko terhadap Keputusan Usaha Hampers: Studi Kasus Pengusaha Hampers Kota Medan - Putri Elda Sari; Muhammad Lathief Ilhamy Nasution; Aqwa Naser Daulay (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
This study aims to analyze the influence of digital promotion, profit potential, and business risk on hamper business decisions in Medan City. In this study, a quantitative approach was used along with a survey. Hamper entrepreneurs in Medan City who have been operating for at least one year were the subjects of this study. The sampling technique applied purposive sampling with a total of 90 respondents. SmartPLS 4.0 software was used to analyze the data collected through questionnaires and processed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. The results showed that digital promotion, profit potential, and business risk each had a positive and significant influence on hamper business decisions in Medan City. In addition, all three variables also influenced business decisions with an R-Square value of 0.585, indicating that the research model could explain 58.5% of the variation in business decisions. These findings indicate that hamper business decisions are influenced by the effectiveness of digital promotion strategies, consideration of profit potential, and an understanding of the business risks faced by entrepreneurs. The results of this study are expected to help hamper entrepreneurs make better and more sustainable business decisions.